The Possibility of Using the Probiotic Starter Culture Lacticaseibacillus rhamnosus LOCK900 in Dry Fermented Pork Loins and Sausages Produced Under Industrial Conditions - Katarzyna Neffe-Skocińska; Anna Okoń; Dorota Zielińska; Piotr Szymański; Barbara Sionek; Danuta Kołożyn-Krajewska (Applied Sciences, 2020)
Probiotic strains used in the production of dry fermented meat should have appropriate technological properties comparable to traditional starter cultures used in meat processing. The problem arises when probiotics are added to a nonsterile food matrix, such as meat, and when it is uncertain whether these microorganisms have dominated the environment. The study aimed to assess the microbiological, physicochemical quality and safety of dry fermented pork loins and sausages with the addition of the probiotic starter culture LOCK900, produced under industrial conditions. Additionally, genetic identification by the PCR method and the presence of LOCK900 in the final products and after storage was done. It was demonstrated by the high number of LAB (>6.0 log cfu g −1) and confirmed the presence in 90% of the probiotic strain LOCK900 in the study of dry fermented meat products during all processing stages. Moreover, the safe and good quality loins and sausages can be stored in refrigerated, anaerobic conditions for 12 weeks, provided that optimized technological conditions are applied. In conclusion, the obtained results of the experiment showed that it is possible to create innovative functional dry fermented pork loins and sausages in a laboratory and then transfer the developed technology to full industrial conditions.